The HIV paradox: perinatal mortality is lower in HIV+ mothers. A case-control study in Ethiopia. (30th September 2020) - Fonzo, M; Dalla Zuanna, T; Sperotto, M; Resti, C; Tsegaye, A; Azzimonti, G; Manenti, F; Putoto, G; Bertoncello, C
Abstract: Background: In Ethiopia, HIV prevalence is 1.2% in 15-49-year-old women, peaking at 3% in aged 40-44. Nationally, efforts have made to provide HIV testing and treatment to all HIV+ subjects, and prevention of mother-to-child transmission. This may imply a closer monitor of health conditions for HIV+ pregnant women. Moreover, antenatal care (ANC) in the third trimester of pregnancy is associated with lower perinatal mortality (PNM). Considering this, we aimed at comparing PNM between HIV+ and HIV- mothers. Methods: The study was conducted in Wolisso Hospital, Oromiya Region, Ethiopia, a second level hospital with a 1, 000, 000-catchment area. Cases were all mothers who experienced a perinatal death before hospital discharge. For each case, two mothers who gave birth to a baby alive until discharge were selected as controls. A regression model was built, considering maternal age, rural-urban residence, grand multiparity, twin pregnancy, maternal ongoing chronic/infectious disease and provision of ANC as potential confounders. Results: Overall, 1175 cases and 2350 controls were included. HIV+ women (n = 71; 2, 0%) showed a crude OR = 0.44 (95%CI: 0.24-0.81) for PNM and an adjusted aOR=0.50 (95%CI: 0.25-0.98) when controlling for the aforementioned confounders, including provision of ANC. While 69, 0% of HIV+ women received specific ANC, only 24, 2% of HIV- women did (p(χ2)<0.001). Conclusions: Our findings show how the risk of PNM is 50% less in HIV+ mothers. Because of their HIV-positive-status, they are more likely to be in contact with healthcare providers and, thus, to have higher chances to be addressed to ANC services. A large part of the contribution seems to reside in activities directly related to HIV control. This evidence supports national policies against HIV and suggests a considerable improvement of PNM by extending high quality ANC to all pregnant Ethiopian women. Paradoxically, HIV stands out for being a health threat that reduces PNM. Key messages: In Wolisso hospital, a second level general hospital in Ethiopia, babies born to HIV+ women have a -50% risk of perinatal death. Extending high quality ANC is worth the effort: removing barriers to access and reaching all pregnant women would lead to a massive reduction in perinatal mortality.